2015
DOI: 10.1007/s10561-015-9521-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between cryopreserved and glycerol-preserved allografts in a partial-thickness porcine wound model

Abstract: Human skin allografts are one of the best temporary biological coverings for severely burned patients. Cryopreserved (CPA) and glycerol-preserved (GPA) allografts are the most widely used types. This study compared the allograft efficiency of both preservation methods under the same conditions. To simulate actual clinical conditions, we used a porcine wound model. In addition, we evaluated the macroscopic and microscopic scoring of graft performance for each method. Porcine cadaver skin 1 mm thick was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Although glycerol has been widely used as a cryoprotectant, its use in preserving the essential qualities of cultured cell sheets at above freezing temperatures pretransplantation has not been explored. It has been reported that pig skin allografts can be successfully preserved with 85% glycerol when kept at 4°C [23, 24]. Studies have shown that a lower concentration of glycerol (<6% in cell culture or intratesticular injection of a 10% glycerol solution) suppresses proliferation [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Although glycerol has been widely used as a cryoprotectant, its use in preserving the essential qualities of cultured cell sheets at above freezing temperatures pretransplantation has not been explored. It has been reported that pig skin allografts can be successfully preserved with 85% glycerol when kept at 4°C [23, 24]. Studies have shown that a lower concentration of glycerol (<6% in cell culture or intratesticular injection of a 10% glycerol solution) suppresses proliferation [25, 26].…”
Section: Discussionmentioning
confidence: 99%